Implementasi Node Sensor untuk Sistem Pengamatan pH Air Pada Budidaya Ikan Air Tawar - Rian Bayu Pambudi; Widhi Yahya; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The information on water conditions in the aquatic field can be beneficial to maintain a good water quality. It can provide benefits especially in fish cultivation water. There are several parameters that affect water quality in freshwater fish culture where one of the parameters is pH or acidity level in water. One study explains that living freshwater organisms can only live at a pH between 6.8 to 8.0 and pH changes can occur at any time. At this time, a device that can measure the pH value or water acidity is a colorimeter, pH indicator and pH meter. The pH observations on these three devices can only perform one time data retrieval so that when used for continuous observations it is less efficient. Realtime monitoring systems can be built by implementing monitoring functions on the Internet of Things where they use sensors and actuators. In this study the authors use Probe Sensor SEN1069 as part of the system that performs data retrieval and Arduino microcontroller as part of the system that controls the sensor. Sensors and microcontrollers take pH data and then process pH data and send it to a server using Websocket communication mechanism. From the test results, the performance of system computing time is 2.505 seconds for computing 1000 data of acid solution or alkaline solution, 16 seconds to observe the change from pH 7.00 to acid solution and 8 seconds from pH 7.00 to alkaline solution.